The Effectiveness of Marmet Techniques, Oxytocin Massage, and Endorphin Massage to Breast-Milk Production on Post Cesarean Section at RSIA Puri Bunda Hospital Malang - Nur Azizah; Rahmania Ambarika (Journal for Quality in Public Health, 2022)
Breast milk is the most ideal food for babies. One of the efforts to increase breast milk production in post partum is to stimulate its natural hormones, namely the hormone prolactin and the hormone oxytocin. There are several interventions to increase the smoothness of breast milk, namely oxytocin massage, endorphin massage, and the marmet technique.The research design used was a quasi-experimental design with a post-test only design. The research sample was 60 post-sectional mothers who were taken using simple random sampling. The independent variables are marmet technique, oxytocin massage, endorphin massage. The dependent variable is post-sectional milk production. Data were collected using a questionnaire and analyzed using the Kuskal Wallis Test with a significance of p <0.05.The results showed that the treatment of the marmet technique for breast milk production was not smooth as many as 15 respondents (75%). The endorphin massage treatment had smooth milk production as many as 17 respondents (85%). Oxytocin massage treatment for milk production was smooth as many as 20 respondents (100%). Based on the Kuskal Wallis Test, it is known that Asymp.Sig. (2-tailed) has a value of 0.0000 which is <0.05, it can be concluded that Ha is accepted, there is a significant difference between breast milk production with the marmet technique, oxytocin massage, and endorphin massage to breast-milk production on post caesarean section women at Puri Bunda Hospital Malang. It was concluded that oxytocin massage and endorphin massage are techniques that have the opportunity to launch breast milk compared to the marmet technique on the production of breast milk for post sectio mothers at Puri Bunda Hospital Malang. It is recommended for further researchers to be able to measure the intensity of oxytocin massage pressure, endorphins, and marmet techniques in order to increase the accuracy of giving oxytocin massage to post caesarean section women.